Coronary Artery Calcium Versus Pooled Cohort Equations Score for Primary Prevention Guidance - Muhlestein, Joseph B.; Knowlton, Kirk U.; Le, Viet T.; Lappe, Donald L.; May, Heidi T.; Min, David B.; Johnson, Kevin M.; Cripps, Shanelle T.; Schwab, Lesley H.; Braun, Shelbi B.; Bair, Tami L.; Anderson, Jeffrey L. (JACC. Cardiovascular imaging, 2022)
This study sought to determine the feasibility of performing an extensive randomized outcomes trial comparing a coronary artery calcium (CAC)- versus a pooled cohort equations (PCE) risk score–based strategy for initiating statin therapy for primary atherosclerotic cardiovascular disease (ASCVD) prevention. Statin therapy is standard for the primary prevention of ASCVD in subjects at increased risk. National guidelines recommend using the American College of Cardiology/American Heart Association PCE risk score to guide a statin recommendation. Whether guidance by a CAC score is equivalent or superior is unknown. CorCal (Effectiveness of a Proactive Cardiovascular Primary Prevention Strategy, With or Without the Use of Coronary Calcium Screening, in Preventing Future Major Adverse Cardiac Events) was a randomized trial consenting 601 patients without known ASCVD, diabetes, or prior statin therapy recruited from primary care clinics and randomized to CAC- (n = 302) or PCE guidance (n = 299) of statin initiation for primary prevention. Enrolled subjects and their physicians made final treatment decisions. Primary outcomes compared the proportion of statin recommendations received and subject adherence over 1 year between CAC- and PCE-arm subjects. Modeled medical costs, adverse effects, and low-density lipoprotein–cholesterol (LDL-C) were additional measures of interest. Subjects were well matched, and 540 (89.9%) completed entry testing and received a protocol-based recommendation. A statin was recommended in 101 (35.9%) CAC-arm and 124 (47.9%) PCE-arm subjects (P = 0.005). Compared to PCE-based recommendations, CAC-arm subjects were reclassified from statin to no statin in 36.0% and from no statin to statin in 5.6% of cases, resulting in a total reclassification of 20.6%. Physicians accepted the study-dictated recommendation to start a statin in 88.1% of CAC-arm vs 75.0% of PCE-arm subjects (P = 0.01). Patient-reported adherence to this recommendation at 3 months was 62.2% vs 42.2%, respectively (P = 0.009). At 1 year, statin adherence remained superior, LDL-C levels were lower, estimated costs were similar or reduced in CAC subjects, and few events occurred. CAC guidance may be a more efficient, personalized, cost-effective, and motivating approach to statin initiation and maintenance in primary prevention. This feasibility phase of CorCal should be regarded as hypothesis-generating with respect to cardiovascular outcomes, which is being addressed in a large, longer-term outcomes trial. (Effectiveness of a Proactive Cardiovascular Primary Prevention Strategy, With or Without the Use of Coronary Calcium Screening, in Preventing Future Major Adverse Cardiac Events [CorCal]; NCT03439267) [Display omitted]